Pengaruh Pendekatan Scaffolding dalam Pembelajaran Matematika terhadap Prestasi Belajar Siswa di MTsN Jambewangi Selopura Blitar - Moh. Nasrul Fuad; Muhammad Zainuddin MZ; Nizar Zakaria (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to test the effect of the scaffolding approach in mathematics learning on student achievement at MTsN Jambewangi Selopuro Blitar. With a quantitative approach and quasi-experimental research type, this study used a randomized post-test group design. Class VIII G as the control class and VIII H as the experimental class, with 37 students each, were selected using cluster sampling techniques. Data were collected through tests and analyzed with the Independent Samples T Test. The results showed that the scaffolding approach had a significant effect on student achievement, so it can be an alternative effective learning method to improve students' ability to understand mathematical concepts. The scaffolding approach is a very effective learning method in improving student achievement, especially in understanding complex mathematical concepts. By providing appropriate assistance and support in the early stages of learning, students can build a strong foundation and improve their abilities gradually. Therefore, the scaffolding approach can be an alternative effective learning method for teachers to improve student learning outcomes.